2016
DOI: 10.28945/3571
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Capability: A Systematic Review and Research Agenda

Abstract: Purpose: Innovation capability is a growing and significant area of academic research. However, there is little attempt to provide a cumulative overview of this phenomenon. The purpose of this systematic review is to synthesize peer reviewed articles published in the area to develop a conceptual framework and to aid future research. Design/Methodology/Approach: The paper adopted a systematic review of literature on innovation capability. The final screening generated 51 articles from 30 journals from 2000-2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 0 publications
0
35
0
3
Order By: Relevance
“…Hence, this area needs to be explored by the HEIs in Oman. In a study conducted by Iddris (2016), who conducted a systemic review on innovation capability in 30 journals from 2000-2015, he reported that there were no formal studies on innovation capability from countries in the Middle East. This made it more difficult for the researchers to find the needed academic literature on innovation, much more, innovation in the academe.…”
Section: Figure 2 Heis With Innovation Practicesmentioning
confidence: 99%
“…Hence, this area needs to be explored by the HEIs in Oman. In a study conducted by Iddris (2016), who conducted a systemic review on innovation capability in 30 journals from 2000-2015, he reported that there were no formal studies on innovation capability from countries in the Middle East. This made it more difficult for the researchers to find the needed academic literature on innovation, much more, innovation in the academe.…”
Section: Figure 2 Heis With Innovation Practicesmentioning
confidence: 99%
“…Through the content analysis of 51 articles from 30 journals published between 2000 and 2015, focusing on how innovation capability is defined, Iddris (2016) suggests that there is a lack of consensus regarding its definition. He states that generally the authors made reference to the terms knowledge transformation, learning, idea generation and processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a systematic review, Iddris (2016) identifies different studies that have all recognized organizational culture as a driving force for innovation capability (for example, Lawson and Samson 2001;Çakar and Ertürk 2010;and Martins and Terblanche 2003). He points out that an organization that promotes the empowerment of employees, tolerance, effective communication between focal firms and significant partners and a positive attitude towards achieving organizational goals can be seen to promote an innovation culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Innovation capability is viewed as a resilient strategic competitive techniques for SMEs in today"s global business environment which is full of intense competition with great growing demand for better quality product, quick response time, unfailing deliveries and new product utilities (Abereijo, Adegbite, Ilori, Adeniyi and Aderemi, 2009). Consequently, this fast changes in technologies, consumers" taste and preferences, as well as overall market condition means that firms" survival, competitive advantage and success depend on its capability to innovate (Yusr, 2016, Iddris, 2016. However, Edwards, Delbridge and Munday (2001) demonstrated that innovation is not just about a abilities, it is about systems, competence and at times luck and unexpected discovery.…”
Section: Innovation Capability and Competitive Advantagementioning
confidence: 99%